2020
DOI: 10.1016/j.heliyon.2020.e05018
|View full text |Cite|
|
Sign up to set email alerts
|

Climate change impacts and adaptations on health of Internally Displaced People (IDP): An exploratory study on coastal areas of Bangladesh

Abstract: Every year thousands of people are being displaced in coastal areas of Bangladesh due to natural calamities associated with climate change, known as Internally Displaced Peoples (IDPs). Climate change adaptation measures play a significant role in coping with the alteration of climatic components, while various forms of barriers hinder the sustainability of adaptation. This research was conducted to understand the perception of IDPs on climate change impact on health in the coastal areas of Bangladesh, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 84 publications
1
12
0
1
Order By: Relevance
“…Retrieved studies focused on rural to urban migration. With the exception of four studies, that mentioned migration was involuntary, [24][25][26][27] other studies did not mention if migration was involuntary or voluntary. Except for one study that adopted a longitudinal design, the remaining studies utilised a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieved studies focused on rural to urban migration. With the exception of four studies, that mentioned migration was involuntary, [24][25][26][27] other studies did not mention if migration was involuntary or voluntary. Except for one study that adopted a longitudinal design, the remaining studies utilised a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…33 Three studies reported general health problems like waterborne (diarrhoea, skin diseases, cholera, jaundice) and vector borne diseases (dengue, chikungunya, malaria), fever and cough. 27,28,50 3.2 | Healthcare access…”
Section: Occupational Health (N = 3)mentioning
confidence: 99%
“…Nous avons aussi plus que jamais besoin d’une perspective mondiale. Des phénomènes climatiques comme les rivières atmosphériques qui ont emporté des routes et inondé des fermes en Colombie-Britannique sont d’une très grande importance localement, mais ces phénomènes font piètre figure face aux sécheresses et aux inondations dans les pays du Sud, qui ont des conséquences dévastatrices pour les populations : famines, migrations forcées et conflits politiques (Leal Filho et al, 2021 ; Kelley et al, 2015 ; Chowdhury et al, 2020 ). C’est la première ministre de la Barbade, Mia Mottley ( 2021 ), qui a posé la question le plus succinctement à la CdP-26 : « Peut-il y avoir paix et prospérité si un tiers du monde vit dans la prospérité et que les deux tiers vivent sous les mers et font face à des menaces catastrophiques pour notre bien-être?…”
Section: éDitorialunclassified
“…Furthermore, we need a global perspective more than ever. While climate events like atmospheric rivers washing out highways and flooding farms in BC are having tremendous significance locally, such climate events pale in comparison to droughts and flooding across the Global South that are devastating large populations of people in the form of famines, forced migration, and political conflict (Leal Filho et al, 2021 ; Kelley et al, 2015 ; Chowdhury et al, 2020 ). Barbados Prime Minister Mia Mottley ( 2021 ) posed the question most succinctly at COP26, “Can there be peace and prosperity in one third of the world if two thirds are under siege and facing calamitous threats to their well-being?”…”
mentioning
confidence: 99%
“…Climate change is one of the most challenging issues of the 21st century having widespread impacts on the societies and environment (IPCC, 2018). It is posing a serious risk to the global community particularly the developing nations who are continuously facing a vulnerable situation with the increase in intensity and frequency of extreme weather events (Chowdhury et al, 2020). A recent report by the IPCC, (2018) highlighted that by 2050, around 150 million people will be displaced due to climate change-induced phenomena around the world.…”
Section: Introductionmentioning
confidence: 99%